The last COVID-19 lockdown in Bhutan: a referral hospital’s response to a community outbreak of the Omicron variant - Monu Tamang; Thinley Dorji; Sangay Tenzin; Choeda Gyaltshen (Bhutan Health Journal, 2024)
This viewpoint outlines the COVID-19 management strategies Central Regional Referral Hospital (CRRH) adopted in Bhutan during the Omicron variant outbreak. The hospital in the high-risk region provided healthcare and public health services to its catchment area during the lockdowns imposed in Bhutan. Specifically, we discuss the hospital’s role in outbreak management, surveillance, isolation, patient care, and non-clinical services. Key strategies including community-based surveillance, isolation in hotel facilities, telemedicine and community engagement are highlighted. We briefly outlined lessons learned from the experience, such as the importance of community involvement and innovative approaches to healthcare delivery during pandemics.